You're so invited : panic less, play more, and get your party on - Najafi, Cheryl (New York : St. Martin's Press, 2012)
Shares ideas for first-time home entertainers, outlining ten fully photographed party plans for such events as birthdays and baby showers while offering suggestions for food and drink preparations, decorating, and having fun while hosting.
Foreword. General preparation tips & advice -- Decorating & decor -- Food & drink -- The parties. Going-away roast -- Yen-for-zen garden get-together -- Martini birthday bash -- Guys-only scotch & cigars gathering -- Tween spa birthday -- Meet & Potatoes dinner party -- Sophisticated retro baby shower -- Elegant Thanksgiving potluck -- Swashbuckling walk-the-plank pirate party -- Holiday coffee drop-in -- Resource guide.
"CherylStyle."
Includes index.
Keywords: Entertaining; Parties -- Planning